Quantum State Preparation for Quantum Key Distribution Using PLC Module - Dan Wu; Shaokang Chen; Pengwei Cui; Junchi Ma; Wei Chen; Jiashun Zhang; Yue Wang; Jianguang Li; Junming An (IEEE Photonics Journal)
Quantum Key Distribution (QKD) is gaining significant interest due to its theoretical guarantee of unconditional security. Integrated optics offers distinct advantages compared to bulk optics, including high stability, flexibility, controllability, and robustness. We develop a planar lightwave circuit (PLC) silica asymmetric Mach-Zehnder interferometer (AMZI) module with temperature system at an accuracy of 0.1 °C including an AMZI chip with a 400ps delay and a single-chip microcomputer. The silica AMZI module is used to encode at Alice, and the same low loss AMZI module is used to decode at Bob at a clock repetition rate of 156 MHz. Two intensity states Z -basis (|0〉, |1〉) and two phase states X-basis (|+〉, |−〉) are prepared at Alice and detected at Bob successfully. The extinction ratio of |0〉 and |1〉 between first-slot and third-slot are about 17 dB. And the interference visibility of |+〉, |−〉 between interference max and min of second-slot are about 88%. The estimated secret key rate and the quantum bit error rate (QBER) using a simulation model for a transmission distance of 20 km is 16.3 kbps and 0.0384, respectively.